In Vitro Callus Induction from Leaf Explants of Vanda sp Stimulated by 2,4-D - Budisantoso, Iman; Amalia, Nurul; Kamsinah, Kamsinah (Biosaintifika: Journal of Biology & Biology Education, 2017)
The addition of growth regulator is one of the critical success factors in in vitro cultures. 2,4-D as a plant regulator in media can stimulate the cell division, enlargement of the explants and promotes the formation and growth of callus. The purpose of this study was to determine the time of callus formation and to determine the best concentration of 2.4-D in inducing the growth of callus from leaf explants of Vanda sp. This research was conducted by experiment with completely randomized design, which consists of six levels of treatment concentration of 2,4-D i.e. 0 ppm; 1 ppm; 1.5 ppm; 2 ppm; 2.5 ppm; and 3 ppm. The parameters observed were the percentage of callus formation and the form of callus from Vanda sp leaf explants. The results were statistically analyzed by using MINITAB program version 17. Analysis of variance (ANOVA) was performed and the difference between means score/value was separated by F test at p < 0.05. The results showed that 2,4-D treatment give significant effect (F 5,12 = 3,20; p = 0,046 < 0,05) on the callus growth time and its percentage. Application of 2 ppm 2.4-D was the best concentration for accelerating the callus growth time (14.3 days after planting) and increasing the percentage of callus formation (83.3%). Most of callus type were proliferative callus (36.11%) and senescence callus (11.11%). The results of this research are very important to grow the callus from Vanda leaves orchid explant because it is very diffucult to grow.